The effect of chloride as catalyst layer contaminant on the degradation of PEMFCs - Paiva Luís, Teresa (2013)
In this work, the effect of chloride as a catalyst contaminant was studied on the performance and durability of a low power open-cathode fuel cell, intended for passive management of water. In an ex-situ study, cyclic voltammetry was used to assess the redox behaviour of platinum in chloride contaminated solutions at room temperature.The cell was operated integrating a range of relative humidity (RH) from ~30 to 80% and temperatures from 5 to 55 ºC. Results indicated that 60% RH is associated to maximum fuel cell performance over the studied temperature range. An examination of the fuel cell components after 100 h of operation revealed that chloride contamination has produced cathode failure associated to catalyst migration favored by operation conditions that allowed platinum particles to break free from their carbon backing and migrate toward the polymer electrolyte. Migration resulted in precipitation with larger mean particle size distribution within the solid electrolyte when compared to the original catalyst layer, rendering a very significant loss of thickness in the cathode material.